“The Pragmatics of Dialogue in Children’s Stories: A Study of the Story ‘The Sudden Absence’.” - Lakhal , Hamza (El Omda in Linguistics and Discourse Analysis, 2021)
Children's stories are considered as one of children's literature genres that is governed by special artistic elements, and based on a set of interconnected events, inspired by reality or fiction that take place in a temporal and spatial environment, and represent various human values with a meaningful end. Children's stories are educational tools that aim to instill positive values in the readers’ mind, satisfy some of their psychological needs, contribute to expanding their perceptions and improve their imaginations, and enrich their sense of adventure and exploration. Children’s literature is the most prominent and well-known child literary art. Hence, in this study, we will try to analyze the story of (the sudden absence) from the perspective of pragmatic linguistics, based on the principle of dialogue entailment and its four rules